1971
DOI: 10.1172/jci106658
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Fibrinogen in Cirrhosis of the Liver

Abstract: A B S T R A C T The metabolism of human fibrinogen labeled with radioactive iodine was studied in 50 patients with documented cirrhosis of the liver and in 35 healthy control subjects. Results in cirrhotic subjects were the following: plasma volume 47 ±+10 ml/kg; plasma fibrinogen concentration 250 ±102 mg/100 ml; total plasma fibrinogen pool 118 ±59 mg/kg, representing 0.73 +0.10 of the total body pool; fibrinogen half-life 2.99 +0.59 days; fractional catabolic rate 0.34 ±0.09 of the plasma pool per day; abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
63
3
3

Year Published

1974
1974
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 52 publications
(35 reference statements)
7
63
3
3
Order By: Relevance
“…High levels of an R-type B12-binding protein with increased sialic acid content have also been demonstrated in patients with hepatoma (25). In addition, T I ME (min) 30 FIGURE 2 Fibrinopeptide release from purified normal and patient fibrinogens. Fibrinogen concentration was 2.7 mg/ml, thrombin concentration was 1.25 U/ml, and temperature was 25°C.…”
Section: Discussionmentioning
confidence: 98%
“…High levels of an R-type B12-binding protein with increased sialic acid content have also been demonstrated in patients with hepatoma (25). In addition, T I ME (min) 30 FIGURE 2 Fibrinopeptide release from purified normal and patient fibrinogens. Fibrinogen concentration was 2.7 mg/ml, thrombin concentration was 1.25 U/ml, and temperature was 25°C.…”
Section: Discussionmentioning
confidence: 98%
“…Tytgat et al (1971) showed a shortened fibrinogen half-life in cirrhotic patients using human fibrinogen laleled with radioactive iodine. This finding, however, may support the concept of chronic DIC rather than overt DIC proposed by the Scandinavian authors, because the investigated cases were relatively stable and thought not to be in overt DIC.…”
Section: Discussionmentioning
confidence: 98%
“…Because of the striking similarity between the hemostatic abnormalities seen in liver cirrhosis and those observed in disseminated intravascular coagulation (DIC), also called consumption coagulopathy, there has been a long and continued debate as to whether DIC is a common feature of, and an important contributor to, hemostatic failure in liver cirrhosis (2-6). The notion of a consumptive coagulopathy in liver cirrhosis was supported by earlier observations (7)(8)(9)(10)(11) that survival of radiolabeled platelets, fibrinogen, and plasminogen was shortened in some patients with liver cirrhosis, and, more importantly, shortened survival of fibrinogen, but not that of platelets or plasminogen, could be prolonged with administration of heparin (7-10) and antithrombin III (ATIII) (11).…”
mentioning
confidence: 89%